Learning Throughout Life: The Information-Knowledge-Wisdom Framework - Marcie Boucouvalas (Educational Considerations, 1987)
The challenge becomes one of transforming an information-rich society into a learning society. . .the question, then, of what are Iegitimate pathways to knowledge is an important one to higher education pursuits.